Evaluating Community Outreach Efforts: A Framework and Approach Based on a National Mental Health Demonstration Project - Brenda M. Joly; Martha Elbaum Williamson; Kimberly Pukstas Bernard; Prashant Mittal; Jennifer Pratt (Journal of MultiDisciplinary Evaluation)
Background:  Community health efforts often include outreach activities designed to increase awareness and ensure uptake of services or programs.  Yet, few comprehensive outreach evaluations exist, particularly those designed to improve access to and use of mental health services.